Reading clubs in Aragón: a descriptive analysis of a social-cultural practice of animation and reading promotion - Agustín Lacruz, Mª del Carmen; Morera Gracia, Eva (Revista General de Información y Documentación, 2016)
The Reading clubs are a type of common cultural and recreational practice today. They carry out activities who involve a lot of people who meet frequently and regularly over very long periods of time. The Reading clubs make a significant impact within the reading practices of each community what is reflected in the use of library services, the trade’s book and public facilities activities’ uses. However, although they are extended and accessible practices, they create an inconspicuous reality. The work’s aim is studying the reading clubs in Aragon today, to contextualize their services promotion and animation of reading. The specific objective is also proposed to characterize the features, types and activities of the clubs, in their contexts and environments, so that it is possible to know and assess the extent of this phenomenon in the autonomous community of Aragon. The study have been consisted of a descriptive analysis, which includes the promoters’ identification and the questionnaire’s development to gather the necessary information
Keywords: Reading Clubs; Reading; Aragon; Reading promotion; Cultural Management; Cultural Practices.